Telemetric intracranial pressure monitoring in patients with hydrocephalus: a systematic literature review - Yangi, Kivanc; Gulick, Daniel W.; Calderon Valero, Carlos E.; Gok, Egemen; D'Saachs, Michael C.; Bassi, Ishaan; On, Thomas J.; Preul, Mark C. (Frontiers in Pediatrics, 2025)
ObjectiveThis systematic literature review sought to examine telemetric intracranial pressure (ICP) monitoring devices, evaluate their operating principles and applications in hydrocephalus management, and highlight their advantages over traditional ICP monitoring methods.Materials and methodsA comprehensive search using Medical Subject Headings terms was conducted in the Medline (via PubMed), Scopus, and Embase databases for articles published in English. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a strict selection process was followed. Three reviewers independently examined the full texts of the selected articles.ResultsA total of 300 articles were retrieved, with 52 meeting the inclusion criteria after removing duplicates and noneligible studies. Telemetric ICP monitoring has been studied since the 1980s, but research remained limited until 2011 (16 [31%] studies), although it increased significantly thereafter (36 [69%] studies). The Raumedic Neurovent-P-tel was introduced in 2009, and 22 of the 36 studies published since 2011 focused solely on Raumedic devices. Likewise, after the Miethke Sensor Reservoir was released in 2015, interest in this field grew, with 9 studies evaluating Miethke devices between 2017 and 2024. Since 2019, 4 studies have reported experiences using both Raumedic and Miethke devices. Among the total of 52 studies, 11 (21%) focused on pediatric patients, 10 (19%) focused on adults, 22 (42%) included both age groups, and 9 (17%) did not specify patient age.ConclusionsTelemetric ICP monitoring has emerged as a valuable tool in managing hydrocephalus, offering continuous, noninvasive monitoring that enhances diagnostic accuracy and treatment adjustments. This review highlights the increasing adoption of these devices and their potential to improve clinical outcomes while reducing hospital admissions and invasive interventions. Despite challenges such as high initial costs and sensor drift, technological advancements and further research could enhance their reliability and expand their applications in neurosurgery.